Development of Animated Video Learning Media in Increasing Learning Interest of Deaf Students at Special Schools - Sri Alda Rabiasa; Dewi Diana Paramata; Muhammad Yusuf; Abdul Haris Odja; Supartin; Dewa Gede Eka Setiawan (Postgraduate, University of Mataram, 2024)
This research is development research (R&D) to obtain quality validation in producing animated video learning media to increase the learning interest of class XI Deaf students at Special Schools in SLB Negeri Kota Gorontalo. The media development model used in this research is the ASSURE model consists of six stages: Analyze learner characteristics; state Objectives; select methods, media, and materials; utilize media and materials; require Learner Participation; and evaluate. The instruments used in this research consisted of student activity observation sheet, learning implementation observation sheet, expert validation sheet, student learning result test sheets, and student questionnaires. The validity of the media received an average score of ≥ 3.00, namely 3.93, and was categorized as very valid overall. The validation indicators obtained an average score of ≥ 3.00 for the overall learning material, namely 3.82 in the very valid category. It is concluded that the validity of animated video learning media in increasing the learning interest of deaf students in SLB Negeri Kota Gorontalo.